Enhancing Elevator Ride Quality through Vector Control Techniques and S-Curve Profiles - Ali, Ali Abdulkareem; Ben Salem, Fatma; Mohammed, Jamal A.-K. (Engineering, Technology & Applied Science Research, 2024)
This study examines motor drive techniques, including Field-Oriented Control (FOC), sensorless FOC, and Direct Torque Control (DTC), to improve elevator ride quality by reducing jerk-sudden changes in acceleration that cause discomfort. A 200 cm tall prototype elevator system was developed, using S-curve velocity profiles alongside the considered control strategies. The system includes a TMS320F28379D DSP-controlled induction motor, sensors, and an encoder to assess performance. Results show that FOC with S-curve profiles reduces jerk by 72–73%, significantly improving comfort compared to the standard trapezoidal profile. Sensorless FOC reduces jerk by 68–71%, providing a cost-effective option, though it faces challenges during downward motion under load. DTC, reduces jerk by 65–68% and results in less smooth travel, especially during downward movement. In comparison, the trapezoidal velocity profile produced higher jerk levels and less ride comfort. This study emphasizes the critical role of control technique selection in enhancing elevator comfort and efficiency.